Which computer-use behaviours are most indicative of cognitive decline? Insights from an expert reference group. (September 2019) - Couth, Samuel; Stringer, Gemma; Leroi, Iracema; Sutcliffe, Alistair G; Gledson, Ann; Bruno, Davide; McDonald, Kathryn R; Montaldi, Daniela; Poliakoff, Ellen; Rust, Jonathan; Thompson, Jennifer C; Brown, Laura JE
Computer use is becoming ubiquitous among older adults. As computer use depends on complex cognitive functions, measuring individuals' computer-use behaviours over time may provide a way to detect changes in their cognitive functioning. However, it is uncertain which computer-use behaviour changes are most likely to be associated with declines of particular cognitive functions. To address this, we convened six experts from clinical and cognitive neurosciences to take part in two workshops and a follow-up survey to gain consensus on which computer-use behaviours would likely be the strongest indicators of cognitive decline. This resulted in a list of 21 computer-use behaviours that the majority of experts agreed would offer a 'strong indication' of decline in a specific cognitive function, across Memory, Executive function, Language and Perception and Action domains. This list enables a hypothesis-driven approach to analysing computer-use behaviours predicted to be markers of cognitive decline.